\({
\subseteq
}\)
:
Sei
\({
v \in \ker
\begin{pmatrix}
\varphi \\
\psi
\end{pmatrix}
}\)
dann gilt
\({
\begin{pmatrix}
0 \\
0
\end{pmatrix}
=
\begin{pmatrix}
\varphi \\
\psi
\end{pmatrix}(v)
=
\begin{pmatrix}
\varphi(v)
\\
\psi(v)
\end{pmatrix}
,
}\)
also
\({
\varphi(v) = 0
}\)
und
\({
\psi(v) = 0.
}\)
\({
\supseteq
}\)
:
Sei
\({
v \in
(\ker \varphi) \cap (\ker \psi)
}\)
dann gilt
\[
\begin{pmatrix}
\varphi \\
\psi
\end{pmatrix}(v)
=
\begin{pmatrix}
\varphi(v)
\\
\psi(v)
\end{pmatrix}
=
\begin{pmatrix}
0 \\
0
\end{pmatrix}
.
\]
\({
\Rightarrow
}\)
:
Es gilt
\({
\varphi(0) = 0
}\),
aufgrund der Injektivität also
\({
\ker \varphi = \varphi^{-1}(0) = \{0\}.
}\)
\({
\Leftarrow
}\)
:
Seien
\({
u, v \in V
}\)
Vektoren mit
\({
\varphi(u) = \varphi(v)
.
}\)
Dann gilt
\[
0 = \varphi(v) - \varphi(u) = \varphi(v - u)
\]
und damit
\({
v - u \in \ker \varphi = \{0\}
.
}\)
Daraus folgt dann
\({
v - u = 0
}\)
und weiter
\({
v = u.
}\)